Socialization of the Benefits of Cat's Whiskers Leaf Extract (Orthisiphon Aristatus) in Healing Wounds - Pranata, Chandra; Darmirani, Yosi (Lembaga Penelitian dan Pengabdian Kepada Masyarakat (LP2M) Institut Kesehatan Medistra Lubuk Pakam, 2024)
Inflammation or wounds are a response to disruption of body tissue due to physical, chemical, or biological factors. Wounds often occur in the layers of the skin, muscles, tissues, and organs of the body. Wounds cause various conditions such as pain, bleeding, and swelling. Cat's whiskers leaves contain flavonoid, polyphenol, and terpenoid compounds that can be useful as antioxidants, antibacterials, and anti-wound agents. The purpose of this socialization is to increase public knowledge about plants around them that can be used for health, such as treating wounds using cat's whiskers leaves. The Community Service activity was carried out through a socialization attended by 25 participants who were residents around the Lubuk Pakam sub-district. The material that was socialized was about the benefits of cat's whiskers leaves in healing wounds, chemical compound content, and the process of extracting cat's whiskers leaves. The level of knowledge of participants was measured based on the pre-test and post-test scores filled in by the Community Service participants to assess the success of the implementation of this socialization activity. The results showed that cat's whiskers leaves can be used as an anti-wound medicine because they are rich in secondary metabolites such as flavonoids, polyphenols, and terpenoids. The process of extracting cat's whiskers leaves can be done through soaking or boiling techniques. After the PkM material was socialized, there was an increase in participant knowledge into the good and very good knowledge categories with percentages of 52% and 28% respectively, where previously knowledge was more dominant in the less and sufficient categories with percentages of 48% and 40%. This PkM activity provides benefits to the community in the form of new knowledge about the benefits of cat's whiskers leaves which can act as an anti-wound medicine.